Connectivity aware tribrid routing framework for a generalized software defined vehicular network - Liyanage, Kushan Sudheera Kalupahana (2020)
Data dissemination is a fundamental, yet one of the pressing issues in vehicular communication due to the associated high dynamicity. The vehicular network topology frequently keeps changing, limiting the lifetime of the links. This imposes serious difficulties in data transmission, especially in multi-hop applications as the vulnerability escalates when the packets are transmitted over multiple hops. The broadcasting based Vehicular Ad-hoc Network (VANET) routing protocols struggle to cope with this dilemma due to the lack of global network information. But, with novel Software Defined Vehicular Network (SDVN), link stability can be better scrutinized pertaining to the availability of global network view. Yet, the architectural challenges in SDVN can limit the availability of network information confining the empowerment of Software Defined Networking (SDN). Thus, in this paper, we introduce a link connectivity aware novel routing framework for a general SDVN acknowledging the limitations in data availability as well. The routing protocol comprises of both centralized and distributed routing techniques and makes use of unicast, broadcast, and store, carry and forward concepts. The resulting tribrid routing framework focuses on finding stable enough shortest routes that can deliver a given set of packets satisfying the required Quality of Services (QoSs) in terms of latency. In case of network uncertainties, the protocol incorporates broadcasting based distributed techniques along with unicast routing. In sparse network conditions, the model aims to deliver the packets in the optimal path with the least store and carry time within the QoS requirement. The routing protocol follows an incremental algorithm where extracted paths are tested for the feasibility on a case by case basis.